Impact of Tariff Wars on Global Economy - Gonchar, Nicholas; Dovzhyk, Olena; Zhokhin, Anatoly; Kozyrski, Wolodymyr; Makhort, Andrii (American Journal of Management Science and Engineering, 2025)
The Ricardian model of world trade based on comparative advantage is not sufficient to justify equal trade relations. The existing model of trade relations does not explain the distribution of income among trading countries. This paper presents a method for building equitable trade relations. Its essence is to present an algorithm for building such trade relations, based on the previously proposed model of world trade, that the trade balance of each country would be equal to zero. Under such conditions, tariff wars would become impossible. It is proved that, provided that the supply structure is consistent with the demand structure, it is always possible to build an equilibrium price vector for which the trade balance of each country is zero. This state of economic equilibrium is called ideal. The article presents an algorithm to build an export structure based on the structure of imports. This algorithm is quite simple and allows for a wide range of applications. Under fairly simple realistic assumptions about the behaviour of countries trading with each other that are subject to tariff restrictions, it is proved that this leads to an increase in the prices of the goods traded by these countries. Among the equilibrium states, there are also those called oversupply states. The latter describes the phenomenon of recession. This contributes to a fall in stock market indices.
Keywords: International Trade Balance; Clearing Markets; Ideal Equilibrium State; Tariff Restrictions; Recession